Instruments d’accountability et équité scolaire dans les systèmes éducatifs d’Europe et du Canada : analyse du PISA 2012 - Voisin, Annelise (Canadian Journal of Education/Revue canadienne de l’éducation, 2022)
This article examines the effectiveness of accountability systems as educational policy tools for improving equity in education systems. Based on a secondary analysis of the PISA 2012 data, this study highlights distinct instrumental components of accountability systems as favoured in education systems in Europe and Canada, which have been little studied by international quantitative studies to date. By discussing their statistical associations with several figures of inequality (inequality in outcomes, inequality of basic skills, inequality of educational achievement opportunities), this study leads to mixed findings regarding the capacity of accountability systems, and the preferred tools on which they rely, to improve equity in education systems in Europe and Canada.